Correlation between Self-Esteem and Academic Achievement among Students of a Selected Nursing College in Mangaluru - Thomas, Litty; Jose, Jisa; Sequera, Sonia Karen Liz; Rose, Anjana (Journal of Health and Allied Sciences NU, 2024)
Background/Objectives People with high self-esteem see themselves as capable, active individuals who can make changes through hard work and higher goals that lead to learning new things. The results in the classroom that demonstrate how successfully a student has fulfilled their learning objectives are referred to as academic achievement. It could allude to achieving major academic achievements, such as receiving a bachelor's degree. In their capacity as health advocates and qualified health care practitioners, nursing students are essential to the public health movement. The aim of this study was to ascertain whether academic achievement and self-esteem are related.Methods The study used a correlational descriptive design. The study sample comprised 197 nursing students from a certain college. The technique of proportionate stratified sampling was employed to choose the students. A checklist of academic achievements, the Rosenberg Self-Esteem Scale, and a baseline proforma were used to collect data.Results Both descriptive and inferential statistics were used in data analysis. The findings of the analysis indicated that there was a marginally favorable correlation between academic success and self-esteem among nursing students. The resulting “r” value (0.158) was statistically significant at the 0.05 level of significance. Consequently, the research hypothesis was accepted, and the null hypothesis was rejected.Conclusion The research project found a weakly positive correlation between academic achievement and self-esteem. The resulting “r” value (0.158) was statistically significant at the 0.05 level of significance. There was a weakly positive correlation between academic achievement and self-esteem among nursing students.
Keywords: nursing students; academic achievement; self-esteem